Preparation and optical properties of Ni-doped PbBiO2Br nanoparticles. (2nd October 2019) - Pan, Jianwei; He, Zuming; Su, Jiangbin; Chen, Rui; Tang, Bin
Abstract: The Pb1−x Nix BiO2 Br (x = 0, 0.1, 0.2, 0.3, 0.4) semiconductor materials were synthesized via a hydrothermal method. The samples were characterized by x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS), field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible diffuse reflection spectroscopy (UV–vis DRS) and photoluminescence (PL) spectroscopy. The results show that the Ni-doped PbBiO2 Br samples are composed of flower-like nanosheets. Ni ions are confirmed to enter the PbBiO2 Br lattice and do not cause the crystal structure changes of PbBiO2 Br, basically maintaining the tetragonal structure. The absorption edge is shifted to higher wavelength, and the corresponding energy gap decreases from 2.49 eV for pristine PbBiO2 Br to 2.30 eV for Ni-doped PbBiO2 Br, and the gradual shift of the FTIR peaks toward lower frequency is observed of the Ni-doped PbBiO2 Br. The PL absorption peaks shift toward the bluish-violet wavelength and their intensity gradually decreases with increasing the Ni content. These can be related to the creation of local defects and further confirm that Ni 2+ ions are indeed included into the PbBiO2 Br lattice. The synthesized Ni-doped PbBiO2 Br nanosheets are expected to be more efficient photocatalytic materials